Geodetic and fibre optic measurements of a full-scale bi-axial compressional test. Issue 347 (3rd March 2016) - Lackner, S.; Lienhart, W.; Supp, G.; Marte, R.
Abstract : Earth filled dams are commonly used as flood prevention dams and for hydroelectric power plants. Their stability is critical for an uninterrupted operation and a reliable protection from catastrophic incidents. During the operation, dams are subjected to lateral loading by hydrostatic pressure. In order to predict the deformation behaviour the material parameters have to be known accurately. Therefore, Graz University of Technology carried out a series of life-size experiments to determine the material parameters of an earth filled dam. Controlled vertical load was applied in these experiments and the resulting deformations were measured with geodetic and fibre optic methods. Single points on the slope were continuously tracked with robotic total stations. In addition, the whole dam surface was monitored using a scanning total station. Finally, relative movements between points on the dam were measured with fibre optic sensors based on fibre Bragg gratings. The achievable measurement precision and the relation between acting load and resulting deformation is investigated in detail for every measurement technique. The authors show in their evaluation that absolute deformations can reliably be detected with the geodetic methods. However, individual loading steps cannot be resolved because of the limited precision of the geodetic measurements. Our results demonstrate that the sensitivity of the monitoring system can be significantly increased with the fibre optic sensors and the scanning data also contribute to assess the stability of the experiment set-up.